Circular RNAs in Cancer – Lessons Learned From microRNAs - Dragomir, Mihnea; Calin, George A. (Frontiers in Oncology, 2018)
Circular RNAs are RNA molecules built from fragments of linear pre-messenger RNAs and other linear RNA species through a process termed “back-splicing” in which the 3’ and 5’ ends are joined together giving rise to a covalently uninterrupted loop. Circular RNAs are not new members of the RNA world; they were first discovered in the early 1990s. The novelty is their abundance in the mammalian cells, as recently thousands of circular RNAs were discovered and annotated. The biogenesis of circular RNAs is a partially characterized process, regulated by three different mechanisms: exon skipping, intron pairing and RNA binding proteins. On the other hand, the function of circular RNAs remains largely unknown and only a handful of singular reports describe in detail the biological roles of some circular transcripts. In a very short period of time numerous circular RNAs were associated with various cancer types, and were also identified in bodily fluids with the potential of being disease specific biomarkers. In this review we briefly describe the biogenesis and function of circular RNAs, and present the circular transcripts that were more than once reported in literature to be associated with cancer. Finally, we point out some of the difficulties encountered in the study of circular RNAs in cancer, as we consider that taking these into account could accelerate and improve our understanding of the biologic and translational use of circular RNAs in human diseases.